Trans Talmud: androgynes and eunuchs in rabbinic literature - Strassfeld, Max K. (University of California Press, 2022)
Trans Talmud places eunuchs and androgynes at the center of rabbinic literature and asks what we can learn from them about Judaism and the project of transgender history. Rather than treating these figures as anomalies to be justified or explained away, Max K. Strassfeld argues that they profoundly shaped ideas about law, as the rabbis constructed intricate taxonomies of gender across dozens of texts to understand an array of cultural tensions. Showing how rabbis employed eunuchs and androgynes to define proper forms of masculinity, Strassfeld emphasizes the unique potential of these figures to not only establish the boundary of law but exceed and transform it. Trans Talmud challenges how we understand gender in Judaism and demonstrates that acknowledging nonbinary gender prompts a reassessment of Jewish literature and law